Inovasi Pembelajaran Problem Based Learning Dalam Mengurangi Kejenuhan Siswa Pada Mata Pelajaran Al qur’an Hadist Kelas XI di MA Zainul Hasan 2 Tahun Ajaran 2024-2025 - Khairul Anam; Mursidah Mursidah (Intellektika : Jurnal Ilmiah Mahasiswa, 2025)
Learning boredom is one of the common problems faced by students, especially at the Madrasah Aliyah level. This issue negatively impacts students' motivation and learning outcomes, which in turn can affect the quality of education. This study aims to implement an innovation in learning through the Problem Based Learning (PBL) approach as an effort to reduce learning boredom among students at MA Zainul Hasan 2 during the 2024-2025 academic year. The method used is Classroom Action Research (CAR) with the Kemmis and McTaggart model, which consists of two cycles. Each cycle includes four stages: planning, action, observation, and reflection. Data collection techniques include observation, questionnaires, and interviews. The results of the study indicate a significant decrease in students' learning boredom levels after the implementation of PBL. The average level of learning boredom decreased from 65% in the first cycle to 45% in the second cycle. This decrease shows that the application of PBL-based learning can have a positive effect in reducing learning boredom and increasing student engagement in the learning process. The PBL-based learning innovation has proven to be effective in creating a more engaging and interactive learning environment, which ultimately can improve students' motivation and enhance their learning outcomes. Thus, this study concludes that the implementation of Problem Based Learning can be an effective solution to overcome learning boredom among Madrasah Aliyah students.